A double heterozygous variant in MYH6 and MYH7 associated with hypertrophic cardiomyopathy in a Japanese Family. Issue 4 (April 2022) - Suzuki, Takanori; Saito, Kazuyoshi; Yoshikawa, Tetsushi; Hirono, Keichi; Hata, Yukiko; Nishida, Naoki; Yasuda, Kazushi; Nagashima, Masami
Abstract: Hypertrophic cardiomyopathy (HCM) is genetically heterogeneous. Different variants associated with HCM have been identified in several cardiac sarcomeric protein genes. We identified the heterozygous missense variant c.2191 C > A p. Pro 731 Thr in the MYH7 gene and the heterozygous frameshift variant c.1091–1092 insTGAA p.Lys364fs*in the MYH6 gene in a Japanese family. Family members with the double variants demonstrated severe phenotypes, such as sudden cardiac-related death and heart failure. These double variants were well segregated and might be responsible for the severity of cardiovascular events in affected family members. These double variants are potentially associated with specific phenotypes in HCM. Further studies are needed to analyze specific gene functions. <Learning objective: Hypertrophic cardiomyopathy (HCM) is genetically heterogeneous and is associated with different variants in sarcomeric protein genes. We identified a heterozygous missense variant in the MYH7 gene and a heterozygous frameshift variant in the MYH6 gene in a Japanese family. These double variants are potentially associated with specific phenotypes in HCM.>